Longitudinal Associations Between Hand Grip Strength and Non-Alcoholic Fatty Liver Disease in Adults: A Prospective Cohort Study - Xia, Yang; Cao, Limin; Liu, Yashu; Wang, Xuena; Zhang, Shunming; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Gu, Yeqing; Wang, Yawen; Zhang, Tingjing; et al. (Frontiers in Medicine, 2021)
Purpose: To determine the longitudinal association between hand grip strength (HGS) and the development of non-alcoholic fatty liver disease (NAFLD) in adults. Design: Cohort study Methods: This study was conducted in a general Chinese population (n=14,154) from 2013-2018. NAFLD was diagnosed by liver ultrasonography during the course of evaluating alcohol consumption. The associations between HGS and NAFLD were assessed using a multivariable Cox proportional hazards regression model. Results: During the study period with a mean follow-up duration of 3.20 years, 2,452 participants developed NAFLD. The risk of NAFLD decreased progressively with increasing HGS in both men and women (P for trend < 0.0001). The multivariate-adjusted hazard ratios (95% confidence intervals) for NAFLD incidence across quartiles of HGS were 1.00 (reference), 0.90 (0.79, 1.02), 0.69 (0.60, 0.79), and 0.44 (0.37, 0.52) for men and 1.00 (reference), 0.82 (0.69, 0.96), 0.54 (0.45, 0.66), and 0.41 (0.33, 0.52) for women, respectively. The interaction terms for body mass index (BMI)- HGS and waist-HGS were significant in men and women (all P < 0.0001). Participants with normal BMIs and waist circumferences had the lowest hazard ratios on subgroup analyses. Sensitivity analysis that defined NAFLD using the hepatic steatosis and fatty liver indices revealed results that were similar to the main analyses. Conclusion: The present study indicates that HGS is inversely associated with the incidence of NAFLD.